Resin film for terminal, method for selecting same, and power storage device

By using a resin layer with specific dynamic viscoelastic properties in an all-solid battery, the problem of insufficient sealing properties of all-solid battery under high temperature conditions is solved, and excellent heat sealing strength is maintained under temperature changes.

CN119581760APending Publication Date: 2025-03-07TOPPAN HOLDINGS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411693735.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2020-12-23
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The heat-resistant properties of the terminal resin film under high temperature conditions are insufficient, resulting in insufficient sealing properties. At the same time, the heat sealing strength decreases after returning to room temperature under high temperature environment.

Method used

A resin layer with specific dynamic viscoelastic properties is adopted. The resin layer has a sub-dispersion peak γ in the range of -130°C to -50°C in dynamic viscoelastic measurement, and a main dispersion peak α in the range of 30°C to 130°C. The peak temperature is controlled by adjusting the plasticizer content to improve the heat resistance and softness of the resin layer.

Benefits of technology

It is achieved to maintain excellent sealing strength at high temperatures and also maintain excellent sealing strength at room temperature, solving the problem of deterioration of heat sealing strength under temperature changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581760A_ABST
    Figure CN119581760A_ABST
Patent Text Reader

Abstract

A terminal resin film according to one aspect of the present disclosure is a terminal resin film disposed so as to cover a part of the outer peripheral surface of a terminal in a power storage device provided with a power storage device main body and a terminal electrically connected to the power storage device main body, has a single-layer structure or a multi-layer structure, and is provided with a resin layer, the resin layer has at least one secondary dispersion peak [gamma] in the range of-130 DEG C to-74 DEG C of a loss tangent tan [delta] curve obtained by dynamic viscoelasticity measurement under 1.0 Hz conditions. The present disclosure also relates to a method for selecting the resin film for a terminal, and to a power storage device provided with the resin film for a terminal.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of application number 2020800903172, application date December 23, 2020, and invention name “Resin film for terminal and selection method thereof, power storage device, and terminal film for power storage equipment”. Technical Field

[0002] The present disclosure relates to a terminal resin film configured in a manner to cover a portion of the peripheral surface of a terminal in a power storage device having a power storage device body and a terminal electrically connected to the power storage device body, and a method for selecting the same. In addition, the present disclosure relates to a power storage device using a terminal resin film. In addition, the present disclosure relates to a terminal film for a power storage device configured in a manner to cover a portion of the peripheral surface of a metal terminal electrically connected to a power storage device body constituting the power storage device. Background Art

[0003] As a power storage device, for example, secondary batteries such as lithium ion batteries, nickel-metal hydride batteries, lead storage batteries, and electrochemical capacitors such as double-layer capacitors are known. Due to the miniaturization of portable devices or the limitation of installation space, the power storage device is required to be further miniaturized, and lithium ion batteries with high energy density have attracted much attention. As a packaging material for lithium ion batteries, metal cans were used in the past, but multilayer films that are lightweight, have high heat dissipation, and can be produced at low cost are gradually used.

[0004] A lithium-ion battery using the above-mentioned multilayer film as a packaging material is called a laminated lithium-ion battery. The packaging material covers the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) to prevent moisture from penetrating into the interior. For example, a laminated lithium-ion battery can be manufactured by the following method: a recess is formed in a portion of the packaging material by cold forming, the battery contents are accommodated in the recess, the remaining portion of the packaging material is folded and the edge portion is sealed by heat sealing (for example, refer to Patent Document 1).

[0005] Laminated lithium-ion batteries have current output terminals (sometimes referred to as "tab leads"). In order to improve the adhesion between the current output terminals and the packaging material, a terminal resin film (sometimes referred to as "tab sealant") is sometimes arranged to cover a portion of the periphery of the current output terminals (for example, see Patent Documents 2 to 4).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-101765

[0009] Patent Document 2: Japanese Patent Application Publication No. 2008-4316

[0010] Patent Document 3: Japanese Patent Application Publication No. 2010-218766

[0011] Patent Document 4: Japanese Patent Application Publication No. 2009-259739 Summary of the invention

[0012] Problems to be Solved by the Invention

[0013] However, as the next generation battery of lithium-ion batteries, a storage device called an all-solid-state battery is being researched and developed. The characteristic of an all-solid-state battery is that, as an electrolytic substance, a solid electrolyte is used instead of an organic electrolyte. Lithium-ion batteries cannot be used at temperatures higher than the boiling point of the electrolyte (about 80°C), but all-solid-state batteries can be used at temperatures exceeding 100°C, and the conductivity of lithium ions can be increased by operating at high temperatures (e.g., 100 to 150°C).

[0014] However, when a laminated all-solid battery is produced using the above-described stack as a packaging material, the sealing properties of the all-solid battery package may become insufficient due to insufficient heat resistance of the terminal resin film.

[0015] Therefore, one aspect of the present disclosure provides a terminal resin film capable of achieving both a sufficiently high level of sealing strength at high temperature and an initial sealing strength, and a method for selecting the same. In addition, a first aspect of the present disclosure provides a power storage device using the terminal resin film.

[0016] In the case of manufacturing a laminated all-solid battery using the above-mentioned stack as a packaging material, the sealing of the all-solid battery package may become insufficient due to insufficient heat resistance of the terminal film. On the other hand, the inventors have found the following problem: from the viewpoint of ensuring heat seal strength in a high temperature environment, when a resin with high heat resistance is used as a terminal film that is melted by heat sealing, the heat seal strength in a room temperature environment decreases when the terminal film is restored to room temperature after working in a high temperature environment.

[0017] Therefore, another aspect of the present disclosure provides a terminal film for an electrical storage device that can ensure excellent heat seal strength in a high-temperature environment and can ensure excellent heat seal strength in a room temperature environment after being exposed to a high-temperature environment.

[0018] Means for solving problems

[0019] A terminal resin film according to one aspect of the present disclosure is a terminal resin film arranged in a manner covering a portion of the outer peripheral surface of a terminal in a storage device having a storage device body and a terminal electrically connected to the storage device body. The terminal resin film has a single-layer structure or a multi-layer structure, and has a resin layer, and the resin layer has at least one secondary dispersion peak γ in the range of -130°C to -50°C of a loss tangent tanδ curve (profile) obtained by dynamic viscoelasticity measurement under 1.0 Hz.

[0020] The secondary dispersion peak γ is an indicator of the molecular motion of the resin material constituting the above-mentioned resin layer, and specifically, it is a parameter reflecting the local torsional motion of the main chain in the crystalline part and the amorphous part of the resin material and the thermal motion of the entire side chain. According to the research of the present inventors, the resin layer that meets the above-mentioned elements regarding the secondary dispersion peak γ contains a resin material that starts molecular motion at a higher temperature, thereby being able to exhibit excellent sealing strength at high temperatures. It should be noted that the lower the temperature at which the secondary dispersion peak γ appears, the more flexible the resin layer is, and the higher the temperature at which the secondary dispersion peak γ appears, the more heat-resistant the resin layer is.

[0021] Preferably, the above-mentioned resin layer has at least one main dispersion peak α in the range of 30°C to 130°C of the curve of tanδ. The main dispersion peak α is a parameter that reflects the micro-Brownian motion of the molecular chain of the amorphous part near the glass transition temperature (Tg) of the resin material contained in the resin layer. According to the research of the present inventors, the resin layer that meets the above-mentioned elements regarding the main dispersion peak α contains a resin material that starts molecular motion at a relatively low temperature (for example, room temperature) and has excellent softness. Therefore, the resin layer can exhibit better sealing strength (initial sealing strength) under room temperature conditions. It should be noted that the lower the temperature at which the main dispersion peak α appears, the more flexible the resin layer is, and the higher the temperature at which the main dispersion peak α appears, the more heat-resistant the resin layer is.

[0022] The resin layer preferably contains a plasticizer. By adjusting the content of the plasticizer in the resin layer, the temperature at which the secondary dispersion peak γ and the main dispersion peak α appear can be controlled. For example, by increasing the content of the plasticizer, the secondary dispersion peak γ and the main dispersion peak α can be shifted to the low temperature side.

[0023] The above-mentioned terminal resin film preferably contains a hydrogen sulfide adsorbing substance. The hydrogen sulfide adsorbing substance may be contained in the above-mentioned resin layer, and may also be contained in other layers when the terminal resin film is a multilayer structure. In an all-solid-state battery, as an electrolyte, for example, a sulfide-based electrolyte, an oxide-based electrolyte, or an organic polymer-based electrolyte may be used. Among these, when a sulfide-based electrolyte is used, hydrogen sulfide is generated when moisture is mixed into the battery, so that the adhesion between the outer peripheral surface of the terminal and the terminal resin film may be reduced. By making the terminal resin film contain a hydrogen sulfide adsorbing substance, excellent sealing strength can be maintained at room temperature and high temperature even after exposure to hydrogen sulfide.

[0024] One aspect of the present disclosure relates to a method for selecting a terminal resin film disposed so as to cover a portion of an outer peripheral surface of a terminal in a power storage device including a power storage device body and a terminal electrically connected to the power storage device body. The selection method includes the following steps.

[0025] (A) a step of measuring the dynamic viscoelasticity of a terminal resin film to be evaluated at 1.0 Hz;

[0026] (B) A step of determining whether or not there is at least one secondary dispersion peak γ in the range of -130°C to -50°C of the tan δ curve obtained by the dynamic viscoelasticity measurement.

[0027] Other aspects of the present disclosure involve a terminal film for an electrical storage device (hereinafter referred to as a "terminal film"), which is configured to cover the outer peripheral surface of a portion of a metal terminal electrically connected to the electrical storage device body constituting the electrical storage device, and the terminal film is composed of a resin composition, which includes: a polyolefin as a first resin; and at least one resin selected from polyester, polyamide, polycarbonate, and polyphenylene ether as a second resin.

[0028] By using the above-mentioned second resin, the heat seal strength of the terminal film in a high temperature environment can be improved. However, the inventors found that when the second resin is used alone, the heat seal strength in a room temperature environment is reduced, making it difficult to ensure excellent heat seal strength in both environments. The above-mentioned second resin is a resin with high heat resistance. Although its performance when used in a high temperature environment has been studied, the changes in the heat seal strength in a room temperature environment before and after exposure to a high temperature environment have not been fully studied so far. Since the all-solid-state battery is repeatedly placed in a high temperature environment when in use and in a room temperature environment when not in use, it is required that the heat seal strength of the terminal film does not deteriorate in both use environments. Therefore, after in-depth research, the inventors found that by combining the above-mentioned first resin and the above-mentioned second resin, the reduction in heat seal strength can be suppressed regardless of whether it is in a high temperature environment or a room temperature environment. That is, according to the above-mentioned terminal film for storage devices, by combining a specific first resin and a specific second resin as the material of the terminal film, excellent heat seal strength can be ensured in a high temperature environment, and excellent heat seal strength can also be ensured in a room temperature environment.

[0029] Preferably, the terminal film for an electrical storage device includes a modified polyolefin modified with a polar group reactive with polyester, polyamide, polycarbonate, or polyphenylene ether.

[0030] In the above-mentioned electrical storage device terminal film, the modified polyolefin is preferably modified with maleic anhydride.

[0031] The compatibility between the first resin and the second resin may not be good, and the dispersibility may be insufficient, so that the above-mentioned combined use effect may not be fully obtained. In contrast, by making the first resin contain a modified polyolefin having a polar group that can react with the second resin, the compatibility between the first resin and the second resin can be improved, thereby improving the dispersibility. As a result, the synergistic effect brought about by the combined use of the first resin and the second resin can be more fully obtained, so that a better heat sealing strength can be ensured in a high temperature environment, and a better sealing strength can also be ensured in a room temperature environment. In addition, in the case where the above-mentioned modified polyolefin is a polyolefin modified by maleic anhydride, the above-mentioned effect can be more fully obtained.

[0032] Here, the first resin may contain: the above-mentioned modified polyolefin, and a polyolefin (unmodified polyolefin) that does not have a polar group that can react with the second resin. Since the modified polyolefin is modified, the melting point and molecular weight tend to decrease, so by using a common polyolefin (unmodified polyolefin) in combination, the reduction of heat sealing strength under high temperature environment can be suppressed. It should be noted that when the modified polyolefin and the unmodified polyolefin are used in combination, the modified polyolefin plays a role as a compatibilizer, thereby improving the dispersibility between the unmodified polyolefin and the second resin.

[0033] In the above-mentioned terminal film for storage device, the polyester or polyamide contained in the terminal film preferably has a crystallinity of 10% or more and less than 70% after heat sealing under the conditions of 260°C, 0.5 MPa, and 3 seconds and cooling at room temperature. By making the crystallinity of the polyester and / or polyamide measured by the above method within the above range, the heat sealing strength in a high temperature environment can be further improved, and the flexibility of the terminal film can be further improved.

[0034] In the terminal film for the above-mentioned power storage device, the terminal film preferably contains a hydrogen sulfide adsorbing substance. The hydrogen sulfide adsorbing substance may be contained in the above-mentioned terminal film, and may also be contained in other layers when the terminal film has a multilayer structure. In an all-solid-state battery, as an electrolyte, for example, a sulfide-based electrolyte, an oxide-based electrolyte, or an organic polymer-based electrolyte may be used. Among these, when a sulfide-based electrolyte is used, hydrogen sulfide is generated when moisture is mixed into the inside of the battery, and the adhesion between the outer peripheral surface of the terminal and the terminal film may be reduced. By making the terminal film contain a hydrogen sulfide adsorbing substance, excellent sealing strength can be maintained at room temperature and high temperature even after exposure to hydrogen sulfide.

[0035] Effects of the Invention

[0036] According to one aspect of the present disclosure, a terminal resin film capable of achieving both high temperature sealing strength and initial sealing strength at a sufficiently high level and a method for selecting the same can be provided. In addition, according to the present disclosure, a storage device using the above-mentioned terminal resin film can be provided. According to other aspects of the present disclosure, a terminal film for storage devices capable of achieving both high temperature sealing strength and initial sealing strength at a sufficiently high level can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] [ Figure 1 ] Figure 1 A perspective view showing an example of an all-solid-state battery.

[0038] [ Figure 2 ] Figure 2 This is a cross-sectional view schematically showing an example of a packaging material for a power storage device.

[0039] [ Figure 3 ] Figure 3 (a)~ Figure 3 (c) is a cross-sectional view schematically showing the structure of a sealant layer included in the packaging material for a power storage device.

[0040] [ Figure 4 ] Figure 4 For along Figure 1 The cross-sectional view taken along the line IV-IV shown schematically shows the structure of a tab (a terminal resin film and a metal terminal) of the all-solid-state battery.

[0041] [ Figure 5 ] Figure 5 (a)~ Figure 5 (c) is a cross-sectional view schematically showing an example of the configuration of the resin film for terminals.

[0042] [ Figure 6 ] Figure 6 It is a plan view schematically showing the evaluation samples prepared in Examples and Comparative Examples. DETAILED DESCRIPTION

[0043] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. It should be noted that in the accompanying drawings, the same or corresponding parts are marked with the same symbols, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.

[0044] <Electrical Storage Device>

[0045] Figure 1 1 is a perspective view showing a schematic configuration of the power storage device according to the present embodiment. Figure 1 In the present invention, an all-solid-state battery is used as an example of the power storage device 100 and described below. It should be noted that: Figure 1 The power storage device having the configuration shown is sometimes referred to as a battery pack or a battery cell.

[0046] The power storage device 100 is an all-solid-state battery, and includes: a power storage device body 50, a packaging material 10, a pair of metal terminals 30, and a terminal resin film (also called a tab seal or terminal film) 40. The power storage device body 50 is a battery body that performs charging and discharging. The packaging material 10 is arranged so as to cover the surface of the power storage device body 50 and to be in contact with a portion of the terminal resin film 40.

[0047] [Packaging materials]

[0048] Figure 2The figure is a cross-sectional view showing an example of a cut surface of the packaging material 10. The packaging material 10 has a multi-layer structure, which includes a base material layer 11, a first adhesive layer 12, a barrier layer 13, an anti-corrosion treatment layer 14, a second adhesive layer 17, and a sealant layer 16 in order from the outside to the inside (the side of the power storage device body 50).

[0049] (Sealing agent layer)

[0050] The sealant layer 16 is a layer that imparts sealing properties by heat sealing to the outer packaging material 10 , and is a layer that is disposed inside and heat-sealed (heat-fused) when the electrical storage device is assembled.

[0051] As the sealant layer 16, for example, thermoplastic resins such as polyolefin, polyamide, polyester, polycarbonate, polyphenylene ether, polyacetal, polystyrene, polyvinyl chloride, and polyvinyl acetate can be used. From the viewpoint of heat resistance and sealing adaptability, polyolefin, polyamide, and polyester are preferably used. It should be noted that when directly laminated on the barrier layer without an adhesive, it is preferred to use a layer modified by an acid, a glycidyl group, or the like in contact with the barrier layer.

[0052] Examples of polyolefin resins include low-density, medium-density, and high-density polyethylenes, ethylene-α-olefin copolymers, polypropylene, and propylene-α-olefin copolymers. In the case of copolymers, the polyolefin resin may be a block copolymer or a random copolymer.

[0053] Examples of polyester resins include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). These polyester resins may be used alone or in combination of two or more. In addition, polyesters obtained by copolymerization of any acid and diol may also be used.

[0054] In order to impart sealing properties, heat resistance and other functionalities, for example, antioxidants, slip agents, flame retardants, anti-blocking agents, light stabilizers, dehydrating agents, tackifiers, nucleating agents, plasticizers and the like may be added.

[0055] The melting peak temperature of the sealant layer varies depending on the application, but when used for a packaging material for an all-solid-state battery, it is preferably 160 to 280° C. from the viewpoint of improving heat resistance.

[0056] Preferably, the sealant layer 16 has at least one secondary dispersion peak γ in the range of -130°C to -50°C of the curve of the loss tangent tanδ obtained by the dynamic viscoelasticity measurement under the condition of 1.0 Hz. By making the sealant layer 16 satisfy this condition, the packaging material 10 can achieve both the sealing strength at high temperature and the initial sealing strength (sealing strength at room temperature) at a sufficiently high level. From the viewpoint of the sealing strength at room temperature and high temperature, the temperature range in which the secondary dispersion peak γ exists is more preferably -120°C to -60°C, and further preferably -110°C to -70°C. When the temperature at which the secondary dispersion peak γ exists is lower than -130°C, the heat resistance of the sealant layer 16 becomes insufficient, and the sealing strength at high temperature may be insufficient. On the other hand, when the temperature at which the secondary dispersion peak γ exists exceeds -50°C, the softness of the sealant layer 16 becomes insufficient, and the sealing strength at room temperature may be insufficient.

[0057] The above-mentioned tanδ can be calculated, for example, by the following method: the packaging material is immersed in an aqueous sodium hydroxide solution to dissolve the barrier layer (metal foil), and a film consisting only of the sealant layer is taken out. According to the method based on JIS K7244-4, a dynamic viscoelasticity apparatus (manufactured by SII, trade name: DMS6100) is used to measure the taken out film under the following conditions, and the loss tangent tanδ is calculated from the loss elastic modulus E" and the storage elastic modulus E'.

[0058] Peeling mode: stretching

[0059] Heating rate: 2℃ / min

[0060] Temperature range: -150~150℃

[0061] Frequency: 1.0Hz

[0062] Preferably, the sealant layer 16 has at least one main dispersion peak α in the range of 30°C to 130°C in the above-mentioned tanδ curve. By making the sealant layer 16 satisfy this condition, the packaging material 10 exhibits a more excellent initial sealing strength (sealing strength at room temperature). From the viewpoint of sealing strength at room temperature, the temperature range in which the main dispersion peak α exists is preferably 40°C to 110°C, more preferably 50°C to 100°C. When the temperature at which the main dispersion peak α exists is lower than 30°C, the heat resistance of the sealant layer 16 becomes insufficient, and the sealing strength at high temperature tends to become insufficient. On the other hand, when the temperature at which the main dispersion peak α exists exceeds 130°C, the softness of the sealant layer 16 becomes insufficient, and the sealing strength at room temperature tends to become insufficient.

[0063] The temperature at which the secondary dispersion peak γ and the main dispersion peak α of the sealant layer 16 appear can be controlled, for example, by the structure of the base resin material contained in the sealant layer 16, the stretch ratio of the sealant layer 16, or the mixing amount of additives (such as plasticizers). The sealant layer 16 contains additives as needed. Examples of additives include plasticizers, antioxidants, slip agents, flame retardants, AB agents, light stabilizers, dehydrating agents, and tackifiers.

[0064] Examples of the base resin material contained in the sealant layer 16 include polyester-based, polyolefin-based, and polyamide-based resins.

[0065] The polyester resin can be obtained by copolymerizing an acid component with a diol component. Examples of the acid component include phthalic acid, terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, cyclohexane dicarboxylic acid, adipic acid, and sebacic acid. Examples of the diol component include ethylene glycol, butanediol, pentanediol, hexanediol, neopentyl glycol, diethylene glycol, polytetramethylene glycol, cyclohexanedimethanol, and propylene glycol. According to the research of the present inventors, the temperature at which the secondary dispersion peak γ of ordinary PET (copolymer of terephthalic acid and ethylene glycol) exists is outside the range of -130°C to -50°C, and the sealing strength at room temperature is insufficient. In the case where a plasticizer is not mixed in the sealant layer 16, the sealant layer 16 preferably contains a polyester resin formed by copolymerizing two or more diol components with an acid component.

[0066] Examples of polyolefin resins include polyethylene and polypropylene resins. Since commonly used polyolefin resins have insufficient heat resistance, polyethylene or polypropylene modified with amide or the like is preferably used.

[0067] Examples of the polyamide-based resin include nylon 6 and nylon 6,6.

[0068] From the viewpoint of adjusting the temperature at which the secondary dispersion peak γ and the main dispersion peak α of the sealant layer 16 appear, the sealant layer 16 preferably contains a plasticizer. As the plasticizer, for example, an ester compound can be used. As specific examples, there can be cited: glycol diesters, adipic acid esters, phthalic acid esters, diacetyl monoacylglycerol derivatives, and esters having an ether skeleton. Although depending on the base resin material of the sealant layer 16, the content of the plasticizer in the sealant layer 16 is preferably 30% by mass or less based on the mass of the sealant layer 16. When an excessive amount of plasticizer is mixed in the sealant layer 16, the temperature at which the secondary dispersion peak γ and the main dispersion peak α appear becomes too low, and the cohesive force tends to decrease.

[0069] The sealant layer 16 may be a single-layer structure or a multi-layer structure of two or more layers (see Figure 3 (a)~ Figure 3(c)). When the sealant layer is a single-layer structure, its thickness is preferably 10 to 300 μm, more preferably 20 to 100 μm. When the thickness of the sealant layer 16 is 10 μm or more, it is easy to ensure the sealing and insulation properties. On the other hand, when it is 300 μm or less, the battery capacity can be ensured.

[0070] Figure 3 (b) is a cross-sectional view schematically showing a sealant layer 16 having a two-layer structure. The sealant layer 16 shown in the figure includes: a first resin layer 16a, and a second resin layer 16b formed on the inner surface of the first resin layer 16a. The first resin layer 16a may be made of a material different from that of the second resin layer 16b, and may have a thickness different from that of the second resin layer 16b. The thickness of the first resin layer 16a and the second resin layer 16b may be, for example, both 5 to 300 μm, or both 20 to 200 μm. Figure 3 As shown in (c), the sealant layer 16 has a three-layer structure and may further include a third resin layer 16c.

[0071] In the case where the electrolyte of the all-solid-state battery is a sulfide-based electrolyte, the sealant layer 16 preferably contains a hydrogen sulfide adsorbing substance. By making the sealant layer 16 contain a hydrogen sulfide adsorbing substance, even after exposure to hydrogen sulfide, excellent sealing strength at room temperature and high temperature can be maintained. As a hydrogen sulfide adsorbing substance, a material having the ability to absorb or adsorb hydrogen sulfide can be used. As specific examples thereof, there can be cited: zinc oxide, amorphous metal silicates, zirconium / lanthanide hydroxides, tetravalent metal phosphates, potassium permanganate, sodium permanganate, aluminum oxide, iron hydroxide, silver sulfate, silver acetate, isocyanate compounds, aluminum silicates, potassium aluminum sulfate, zeolite, activated carbon, amine compounds and ionomers.

[0072] Based on the mass of the sealant layer 16, the content of the hydrogen sulfide adsorbing substance in the sealant layer 16 is preferably 1 to 50 mass %, more preferably 2 to 25 mass %, and further preferably 5 to 15 mass %. By making the content of the hydrogen sulfide adsorbing substance in the sealant layer 16 to be 1 mass % or more, the adsorption effect of hydrogen sulfide can be exerted. On the other hand, by making it 50 mass % or less, the sealant layer 16 can have both tightness and sealant adaptability. In the case where the sealant layer 16 is a multi-layer structure, all or part of the layers may contain the hydrogen sulfide adsorbing substance. It should be noted that the layers other than the sealant layer 16 in the packaging material 10 (for example, the second adhesive layer 17) may also contain a sulfide-based electrolyte, but from the viewpoint of the content of the hydrogen sulfide adsorbing substance, it is preferred that at least the sealant layer 16 contains the hydrogen sulfide adsorbing substance.

[0073] (Base material layer)

[0074] The base material layer 11 has the following effects: it imparts heat resistance in the sealing process when manufacturing the power storage device, and suppresses the occurrence of pinholes that may be caused during molding or circulation. In particular, in the case of packaging materials for large-scale power storage devices, it can also impart scratch resistance, chemical resistance, insulation, etc.

[0075] The base material layer 11 is preferably a layer composed of a resin film formed of an insulating resin. Examples of the resin film include stretched or unstretched films such as polyester films, polyamide films, polypropylene films, and polyphenylene sulfide films. The base material layer 11 may be a single-layer film composed of any one of these resin films, or a laminated film composed of two or more of these resin films.

[0076] Among these, as the base material layer 11, from the viewpoint of excellent formability, preferably a polyester film and a polyamide film, more preferably a polyamide film. These films are preferably biaxially stretched films. As the polyester resin constituting the polyester film, for example, polyethylene terephthalate can be cited. As the polyamide resin constituting the polyamide film, for example, nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 6,10, poly(m-xylene adipamide) (MXD6), nylon 11, nylon 12, etc. can be cited. Among these, from the viewpoint of excellent heat resistance, puncture strength and impact strength, nylon 6 (ONy) is preferred.

[0077] Examples of the stretching method for the biaxially stretched film include sequential biaxial stretching, tubular biaxial stretching, and simultaneous biaxial stretching. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably stretched by tubular biaxial stretching.

[0078] The thickness of the base layer 11 is preferably 6 to 40 μm, more preferably 10 to 30 μm. When the thickness of the base layer 11 is 6 μm or more, the pinhole resistance and insulation of the packaging material 10 tend to be improved. When the thickness of the base layer 11 exceeds 40 μm, the total thickness of the packaging material 10 tends to increase.

[0079] (First Adhesive Layer)

[0080] The first adhesive layer 12 is a layer that bonds the substrate layer 11 and the barrier layer 13 together. Specifically, for example, the material constituting the first adhesive layer 12 includes a polyurethane resin obtained by allowing a difunctional or higher-functional isocyanate compound to act on a main agent such as a polyester polyol, a polyether polyol, an acrylic polyol, a carbonate polyol, etc. The above-mentioned various polyols can be used alone or in combination of two or more, depending on the functions and performance required of the packaging material. In addition, various other additives or stabilizers can be mixed in the above-mentioned polyurethane resin according to the performance required of the adhesive.

[0081] The thickness of the first adhesive layer 12 is not particularly limited, but is preferably 1 to 10 μm, more preferably 3 to 7 μm, for example, from the viewpoint of obtaining desired adhesive strength, followability, and processability.

[0082] (Barrier layer)

[0083] The barrier layer 13 has a water vapor barrier property that prevents moisture from entering the interior of the power storage device. In addition, the barrier layer 13 has ductility for deep drawing. As the barrier layer 13, various metal foils such as aluminum, stainless steel, and copper, as well as metal vapor-deposited films, inorganic oxide vapor-deposited films, carbon-containing inorganic oxide vapor-deposited films, and films provided with these vapor-deposited films can be used. From the aspects of mass (specific gravity), moisture resistance, processability, and cost, metal foil is preferred, and aluminum foil is more preferred.

[0084] As aluminum foil, from the perspective of being able to impart the desired ductility during molding, it is particularly preferred to use soft aluminum foil that has been annealed, but in order to further impart pinhole resistance and ductility during molding, it is more preferred to use iron-containing aluminum foil. The iron content in the aluminum foil is preferably 0.1 to 9.0 mass %, more preferably 0.5 to 2.0 mass % in 100 mass % of aluminum foil. By making the iron content 0.1 mass % or more, a packaging material 10 with better pinhole resistance and ductility can be obtained. By making the iron content 9.0 mass % or less, a packaging material 10 with better softness can be obtained. Untreated aluminum foil can be used, but it is preferred to use aluminum foil that has been degreased. When the aluminum foil is degreased, only one side of the aluminum foil can be degreased, or both sides can be degreased.

[0085] The thickness of the barrier layer 13 is not particularly limited, but is preferably 9 to 200 μm, more preferably 15 to 100 μm, in consideration of barrier properties, pinhole resistance, and processability.

[0086] (Anti-corrosion treatment layer)

[0087] The anticorrosion treatment layer 14 is a layer provided to prevent corrosion of the barrier layer 13. The anticorrosion treatment layer 14 can be formed by, for example, degreasing treatment, hydrothermal reforming treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.

[0088] As degreasing treatment, acid degreasing or alkali degreasing can be cited. As acid degreasing, methods such as using a single inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or fluoric acid, or using a mixed solution thereof, etc. can be cited. In addition, as acid degreasing, especially when aluminum foil is used as the barrier layer 13, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound such as monosodium ammonium difluoride in the above-mentioned inorganic acid, not only can the degreasing effect of aluminum be obtained, but also a passive aluminum fluoride can be formed, which is effective in terms of fluorine acid resistance. As alkali degreasing, methods such as using sodium hydroxide can be cited.

[0089] Examples of the hydrothermal modification treatment include a boehmite treatment in which an aluminum foil is immersed in boiling water to which triethanolamine has been added. Examples of the anodic oxidation treatment include an aluminate treatment.

[0090] As chemical conversion treatment, there are immersion type and coating type. As immersion type chemical conversion treatment, for example, there are chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or various chemical conversion treatments consisting of mixed phases thereof. On the other hand, as coating type chemical conversion treatment, there is a method of coating a coating agent having an anticorrosive function on the barrier layer 13.

[0091] Among these anti-corrosion treatments, when at least a portion of the anti-corrosion treatment layer is formed by any one of hydrothermal modification, anodic oxidation, and chemical conversion treatment, it is preferred to perform the above-mentioned degreasing treatment in advance. It should be noted that when a metal foil that has been subjected to a degreasing treatment such as a metal foil that has undergone an annealing process is used as the barrier layer 13, it is not necessary to perform the degreasing treatment again when forming the anti-corrosion treatment layer 14.

[0092] The coating agent used for the coating type chemical conversion treatment preferably contains trivalent chromium. In addition, the coating agent may contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers described below.

[0093] In the above-mentioned treatments, especially in the hydrothermal modification treatment and the anodizing treatment, the surface of the aluminum foil is dissolved by a treatment agent, thereby forming an aluminum compound (boehmite, aluminate) with excellent corrosion resistance. Therefore, a co-continuous structure is formed from the barrier layer 13 using the aluminum foil to the anti-corrosion treatment layer 14, so that the above-mentioned treatment is included in the definition of the chemical conversion treatment. On the other hand, as described later, the anti-corrosion treatment layer 14 can also be formed using only a simple coating method that is not included in the definition of the chemical conversion treatment. As an example of this method, there can be cited: a method of using a sol of a rare earth element oxide such as cerium oxide with an average particle size of less than 100 nm as a material that has an anti-corrosion effect on aluminum (corrosion inhibitor effect) and is also suitable for environmental aspects. By using this method, even a general coating method can be used to impart an anti-corrosion effect to metal foils such as aluminum foil.

[0094] As the sol of the above-mentioned rare earth element oxide, for example, there can be listed: sols using various solvents such as water, alcohol, hydrocarbon, ketone, ester, ether, etc. Among them, water-based sols are preferred. In the above-mentioned rare earth element oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid or their salts, acetic acid, malic acid, ascorbic acid, lactic acid, etc. can be used as dispersion stabilizers to stabilize the dispersion. Among these dispersion stabilizers, phosphoric acid is particularly expected, which in the packaging material 10 can (1) stabilize the dispersion of the sol; (2) improve the adhesion with the barrier layer 13 by utilizing the aluminum chelating ability of phosphoric acid; (3) even at low temperatures, phosphoric acid is easily dehydrated and condensed, thereby improving the cohesion of the anti-corrosion treatment layer 14 (oxide layer), etc.

[0095] The anti-corrosion treatment layer 14 formed by the rare earth element oxide sol is an aggregate of inorganic particles, so even after the drying and curing process, the cohesion of the layer itself may be reduced. Therefore, in this case, in order to supplement the cohesion, the anti-corrosion treatment layer 14 is preferably composited with the following anionic polymer or cationic polymer.

[0096] The anticorrosion treatment layer is not limited to the above-mentioned layer. For example, it can also be formed by using a treatment agent in which phosphoric acid and a chromium compound are mixed in a resin binder (aminophenol, etc.) as a coating type chromate as a known technology. If this treatment agent is used, a layer having both anticorrosion function and tight adhesion can be formed. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent formed by liquefying a rare earth element oxide sol and a polycationic polymer or a polyanionic polymer in advance can be used to form a layer having both anticorrosion function and tight adhesion.

[0097] Regardless of whether it is a multilayer structure or a single layer structure, the mass per unit area of ​​the anticorrosion treatment layer is preferably 0.005 to 0.200 g / m2 , more preferably 0.010 to 0.100 g / m 2 If the mass per unit area is 0.005 g / m 2 If the mass per unit area exceeds 0.200 g / m 2 , the anti-corrosion function will not change much. On the other hand, when using rare earth element oxide sol, when the coating is thick, the curing caused by the heat during drying is insufficient, which may be accompanied by a decrease in cohesive force. It should be noted that the thickness of the anti-corrosion treatment layer 14 can be converted from its specific gravity.

[0098] From the perspective of the adhesion between the sealant layer and the barrier layer, the anti-corrosion treatment layer can be, for example, a method containing cerium oxide, 1 to 100 parts by mass of phosphoric acid or phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer; it can also be a method formed by subjecting the barrier layer 13 to a chemical conversion treatment; it can also be a method formed by subjecting the barrier layer to a chemical conversion treatment and containing a cationic polymer.

[0099] (Second Adhesive Layer)

[0100] The second adhesive layer 17 is a layer for bonding the barrier layer 13 formed with the anticorrosion treatment layer 14 and the sealant layer 16. For the second adhesive layer 17, a conventional adhesive for bonding the barrier layer 13 and the sealant layer 16 can be used.

[0101] When the anti-corrosion treatment layer 14 has a layer containing at least one polymer selected from the group consisting of the above-mentioned cationic polymers and anionic polymers, the second adhesive layer 17 is preferably a layer containing a compound reactive with the above-mentioned polymer contained in the anti-corrosion treatment layer 14 (hereinafter also referred to as a "reactive compound").

[0102] For example, when the anticorrosion treatment layer 14 contains a cationic polymer, the second adhesive layer 17 contains a compound reactive with the cationic polymer. When the anticorrosion treatment layer 14 contains an anionic polymer, the second adhesive layer 17 contains a compound reactive with the anionic polymer. In addition, when the anticorrosion treatment layer 14 contains a cationic polymer and an anionic polymer, the second adhesive layer 17 contains a compound reactive with the cationic polymer and a compound reactive with the anionic polymer. However, the second adhesive layer 17 does not necessarily have to contain the above two compounds, and may also contain a compound reactive with both the cationic polymer and the anionic polymer. Here, "reactive" means forming a covalent bond with a cationic polymer or an anionic polymer. In addition, the second adhesive layer 17 may further contain an acid-modified polyolefin resin.

[0103] Examples of the compound reactive with the cationic polymer include at least one compound selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxyl group, and a compound having an oxazoline group.

[0104] As these polyfunctional isocyanate compounds, glycidyl compounds, compounds having carboxyl groups, and compounds having oxazoline groups, polyfunctional isocyanate compounds, glycidyl compounds, compounds having carboxyl groups, and compounds having oxazoline groups previously exemplified as crosslinking agents for making cationic polymers into crosslinked structures, etc. Among these, polyfunctional isocyanate compounds are preferred because of their high reactivity with cationic polymers and the ease with which crosslinked structures are formed.

[0105] As the compound reactive with anionic polymer, at least one compound selected from the group consisting of glycidyl compounds and compounds with oxazoline groups can be listed. As these glycidyl compounds and compounds with oxazoline groups, glycidyl compounds previously exemplified as crosslinking agents for making cationic polymers into crosslinked structures, compounds with oxazoline groups, etc. can be listed. Among these, glycidyl compounds are preferred from the aspect of high reactivity with anionic polymers.

[0106] When the second adhesive layer 17 contains an acid-modified polyolefin resin, the reactive compound preferably also has reactivity with the acidic group in the acid-modified polyolefin resin (i.e., forms a covalent bond with the acidic group). Thus, the adhesion to the anti-corrosion treatment layer 14 is further improved. In addition, the acid-modified polyolefin resin becomes a cross-linked structure, and the solvent resistance of the packaging material 10 is further improved.

[0107] The content of the reactive compound is preferably an equal amount to 10 times the amount of the acidic group in the acid-modified polyolefin resin. If it is equal or more, the reactive compound fully reacts with the acidic group in the acid-modified polyolefin resin. On the other hand, when it exceeds 10 times the amount, the crosslinking reaction with the acid-modified polyolefin resin is fully saturated, so there are unreacted products, and various properties may be reduced. Therefore, the content of the reactive compound is preferably, for example, 5 to 20 parts by mass (solid content ratio) relative to 100 parts by mass of the acid-modified polyolefin resin.

[0108] The acid-modified polyolefin resin is a material obtained by introducing an acid group into a polyolefin resin. Examples of the acid group include a carboxyl group, a sulfonic acid group, an anhydride group, and the like, with maleic anhydride group and (meth) acrylic acid group being particularly preferred. For example, the same modified polyolefin resin as that used for the sealant layer 16 can be used as the acid-modified polyolefin resin.

[0109] The second adhesive layer 17 may contain various additives such as a flame retardant, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, and a tackifier.

[0110] As the adhesive forming the second adhesive layer 17, for example, there can be listed: a polyurethane resin obtained by allowing a difunctional or higher-functional isocyanate compound to act on a main agent such as polyester polyol, polyether polyol, acrylic polyol, carbonate polyol, etc.; or an epoxy resin obtained by allowing an amine compound or the like to act on a main agent having an epoxy group, etc., which are preferred from the viewpoint of heat resistance.

[0111] The thickness of the second adhesive layer 17 is not particularly limited, but is preferably 1 to 10 μm, more preferably 2 to 7 μm, from the viewpoint of obtaining desired adhesive strength and processability.

[0112] [Metal Terminal]

[0113] Figure 4 for Figure 1 The cross-sectional view of the terminal resin film and the metal terminal along the IV-IV line is shown. Among the pair of metal terminals 30, 30, one metal terminal 30 is electrically connected to the positive electrode of the power storage device body 50, and the other metal terminal 30 is electrically connected to the negative electrode of the power storage device body 50. The pair of metal terminals 30, 30 extend from the power storage device body 50 to the outside of the packaging material 10. The shape of the pair of metal terminals 30, 30 can be set to a flat plate shape, for example.

[0114] Metal can be used as the material of the metal terminal 30. The metal used as the material of the metal terminal 30 can be determined by considering the structure of the power storage device body 50 and the materials of its components. For example, when the power storage device 100 is an all-solid-state battery, aluminum is preferably used as the material of the metal terminal 30 connected to the positive electrode of the power storage device body 50. Copper or nickel having a nickel-plated layer formed on the surface is preferably used as the material of the metal terminal 30 connected to the negative electrode of the power storage device body 50.

[0115] The thickness of the metal terminal 30 depends on the size and capacity of the all-solid-state battery. In the case of a small all-solid-state battery, for example, the thickness of the metal terminal 30 can be set to 50 μm or more. In the case of a large all-solid-state battery for power storage / vehicle use, for example, the thickness of the metal terminal 30 can be appropriately set within the range of 100 to 500 μm.

[0116] [Resin film for terminal]

[0117] like Figure 4 As shown, the terminal resin film 40 is arranged to cover a portion of the outer peripheral surface of the metal terminal 30. By arranging the terminal resin film 40 between the metal terminal 30 and the packaging material 10, the sealing and insulation properties of the power storage device 100 can be further improved. The terminal resin film 40 has heat resistance equal to or higher than that of the above-mentioned sealant layer 16 and base material layer 11.

[0118] The terminal resin film 40 includes a resin layer 40a, and the resin layer 40a has at least one secondary dispersion peak γ in the range of -130°C to -50°C of the loss tangent tanδ curve obtained by dynamic viscoelasticity measurement under 1.0 Hz. The terminal resin film 40 has a single-layer structure or a multi-layer structure. In the case where the terminal resin film 40 is a single-layer structure, the terminal resin film 40 is composed of the resin layer 40a (see Figure 5 (a)). When the terminal resin film 40 has a multi-layer structure, the terminal resin film 40 only needs to include at least one resin layer (resin layer 40a) that satisfies the above conditions (see Figure 5 (b) and Figure 5 (c)) It should be noted that, when the resin film 40 for terminals has a multi-layer structure, it is preferred that all layers are made of the same type of resin material from the viewpoint of adhesion between adjacent layers.

[0119] By providing the terminal resin film 40 with a resin layer 40a, the terminal resin film 40 can achieve both the sealing strength at high temperature and the initial sealing strength (sealing strength at room temperature) at a sufficiently high level. From the viewpoint of the sealing strength at room temperature and high temperature, the temperature range in which the secondary dispersed peak γ exists is preferably -120°C to -60°C, and more preferably -110°C to -70°C. When the temperature at which the secondary dispersed peak γ exists is lower than -130°C, the heat resistance of the resin layer 40a becomes insufficient, and the sealing strength at high temperature may be insufficient. On the other hand, when the temperature at which the secondary dispersed peak γ exists exceeds -50°C, the softness of the resin layer 40a becomes insufficient, and the sealing strength at room temperature may be insufficient.

[0120] The above tanδ can be calculated, for example, by the following method: the terminal resin film 40 is measured under the following conditions using a dynamic viscoelasticity apparatus (manufactured by SII, trade name: DMS6100) according to a method based on JIS K7244-4, and the loss tangent tanδ is calculated from the loss modulus E″ and the storage modulus E′.

[0121] Peeling mode: stretching

[0122] Heating rate: 2℃ / min

[0123] Temperature range: -150~150℃

[0124] Frequency: 1.0Hz

[0125] Preferably, the resin layer 40a has at least one main dispersion peak α in the range of 30°C to 130°C in the above-mentioned tanδ curve. By making the resin layer 40a satisfy this condition, the terminal resin film 40 exhibits a more excellent initial sealing strength (sealing strength at room temperature). From the viewpoint of sealing strength at room temperature, the temperature range in which the main dispersion peak α exists is preferably 40°C to 110°C, and more preferably 50°C to 100°C. When the temperature at which the main dispersion peak α exists is lower than 30°C, the heat resistance of the resin layer 40a becomes insufficient, and the sealing strength at high temperature tends to become insufficient. On the other hand, when the temperature at which the main dispersion peak α exists exceeds 130°C, the softness of the resin layer 40a becomes insufficient, and the sealing strength at room temperature tends to become insufficient.

[0126] The temperature at which the secondary dispersion peak γ and the main dispersion peak α of the resin layer 40a appear can be controlled, for example, by the structure of the base resin material contained in the resin layer 40a, the stretching ratio of the resin layer 40a, or the mixing amount of additives (such as plasticizers). The resin layer 40a contains additives as needed. Examples of additives include plasticizers, antioxidants, slip agents, flame retardants, AB agents, light stabilizers, dehydrating agents, and tackifiers.

[0127] Examples of the base resin material contained in the terminal resin film 40 include polyester-based, polyolefin-based, and polyamide-based resins.

[0128] The polyester resin can be obtained by copolymerizing an acid component with a diol component. Examples of the acid component include phthalic acid, terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, cyclohexane dicarboxylic acid, adipic acid and sebacic acid. Examples of the diol component include ethylene glycol, butanediol, pentanediol, hexanediol, neopentyl glycol, diethylene glycol, polytetramethylene glycol, cyclohexanedimethanol and propylene glycol. According to the research of the present inventors, the temperature at which the secondary dispersion peak γ of ordinary PET (copolymer of terephthalic acid and ethylene glycol) exists is outside the range of -130°C to -50°C, and the sealing strength at room temperature is insufficient. In the case where a plasticizer is not mixed in the resin layer 40a, the resin layer 40a preferably contains a polyester resin formed by copolymerizing two or more diol components with an acid component.

[0129] As polyolefin resins, polyethylene and polypropylene resins can be cited. Since the heat resistance of commonly used polyolefin resins is insufficient, polyethylene or polypropylene modified by amide or the like is preferably used. In addition, from the viewpoint of the close adhesion between the metal terminal 30 and the terminal resin film 40, the base resin material of the terminal resin film 40 is preferably a polyolefin modified by an acid such as carboxylic acid or maleic anhydride or modified by amide.

[0130] Examples of the polyamide-based resin include nylon 6 and nylon 6,6.

[0131] From the viewpoint of adjusting the temperature at which the secondary dispersion peak γ and the main dispersion peak α of the resin layer 40a appear, the resin layer 40a preferably contains a plasticizer. As the plasticizer, for example, an ester compound can be used. As specific examples, glycol diesters, adipic acid esters, phthalic acid esters, diacetyl monoacylglycerol derivatives, and esters having an ether skeleton can be cited. Although depending on the base resin material of the resin layer 40a, the content of the plasticizer in the resin layer 40a is preferably 30% by mass or less based on the mass of the resin layer 40a. When an excessive amount of plasticizer is mixed in the resin layer 40a, the temperature at which the secondary dispersion peak γ and the main dispersion peak α appear becomes too low, and the cohesive force tends to decrease.

[0132] When the terminal resin film 40 is a multilayer structure, the resin layer 40a may be arranged on the side in contact with the metal terminal 30 or on the side in contact with the packaging material 10. When the terminal resin film 40 is composed of three or more layers, the resin layer 40a may be arranged between the resin layer 40b and the resin layer 40c (see Figure 5 (c)).

[0133] From the viewpoint of embedding property and insulation property, the thickness of the terminal resin film 40 is preferably 15 μm or more, more preferably 30 to 300 μm, and further preferably 50 to 200 μm.

[0134] When the electrolyte of the all-solid battery is a sulfide-based electrolyte, the terminal resin film 40 preferably contains a hydrogen sulfide adsorbing substance. By making the terminal resin film 40 contain a hydrogen sulfide adsorbing substance, even after exposure to hydrogen sulfide, excellent sealing strength can be maintained at room temperature and high temperature. Examples of the hydrogen sulfide adsorbing substance include the above-mentioned hydrogen sulfide adsorbing substances.

[0135] Based on the mass of the terminal resin film 40, the content of hydrogen sulfide adsorbing substances in the terminal resin film 40 is preferably 1 to 50 mass %, more preferably 2 to 25 mass %, and further preferably 5 to 15 mass %. By making the content of hydrogen sulfide adsorbing substances in the terminal resin film 40 to be 1 mass % or more, the absorption effect or adsorption effect of hydrogen sulfide can be exerted. On the other hand, by making it 50 mass % or less, the terminal resin film 40 can have both tightness and sealant adaptability. In the case where the terminal resin film 40 has a multi-layer structure, from the viewpoint of tightness to the metal terminal 30, the layer in contact with the metal terminal 30 preferably does not contain hydrogen sulfide adsorbing substances. That is, the layer in contact with the packaging material 10 (for example, Figure 5 (b) The resin layer 40a or Figure 5 The resin layers 40a and 40c in (c) preferably contain a hydrogen sulfide adsorbing substance. When the terminal resin film 40 is composed of three or more layers, the intermediate layer (for example, Figure 5 The resin layer 40a) in (c) preferably contains a hydrogen sulfide adsorbing substance.

[0136] [Selection method of resin film for terminal]

[0137] The method for selecting a terminal resin film can be implemented based on the contents of the above-mentioned embodiment. That is, the selection method is a method for selecting a terminal resin film that is arranged in a manner to cover a portion of the outer peripheral surface of a terminal in a storage device having a storage device body and a terminal electrically connected to the storage device body, and the method only needs to include the following steps: (A) a step of performing a dynamic viscoelasticity measurement on the terminal resin film of the evaluation object under the condition of 1.0 Hz; and (B) a step of determining whether there is at least one secondary dispersion peak γ in the range of -130°C to -50°C of the tanδ curve obtained by the above-mentioned dynamic viscoelasticity measurement. The selection method can appropriately use the matters described in the above-mentioned embodiment.

[0138] [Other forms of resin film for terminal]

[0139] The terminal resin film 40 (hereinafter referred to as the terminal film 40) can be composed of a resin composition, which includes a polyolefin as a first resin; and at least one resin selected from polyester, polyamide, polycarbonate, polyphenylene ether (hereinafter referred to as polyester, etc.) as a second resin. The terminal film 40 has a single-layer structure or a multi-layer structure. In the case where the terminal film 40 is a single-layer structure, the terminal film 40 is composed of a resin layer 40a (refer to Figure 5 (a)). When the terminal film 40 has a multi-layer structure, the terminal film 40 only needs to include at least one resin layer (resin layer 40a) that satisfies the above conditions (see Figure 5 (b) and Figure 5 (c)). It should be noted that, when the terminal film 40 is a multilayer structure, from the viewpoint of the close adhesion between adjacent layers, it is preferred that all layers are composed of the same resin material. It should be noted that, in this case, similarly to the terminal resin film 40, the sealant layer 16 can also be composed of a resin composition, the resin composition comprising a polyolefin as a first resin; and at least one resin selected from polyester, polyamide, polycarbonate, and polyphenylene ether as a second resin.

[0140] The terminal film 40 preferably contains a modified polyolefin modified by a polar group that can react with a polyester or the like as the second resin. By providing the terminal film 40 with a resin layer 40a having the above-mentioned composition, the terminal film 40 can achieve both a sealing strength at high temperature and an initial sealing strength (sealing strength at room temperature) at a sufficiently high level. The following is an example of the resin constituting the terminal film 40.

[0141] (Polyolefin resin)

[0142] As the polyolefin resin, polyethylene (LDPE, LLDPE, HDPE), polypropylene (homopolymer, block, random), polybutene, etc. can be used. From the viewpoint of heat resistance and flexibility, polypropylene is preferably used, and block polypropylene is more preferably used.

[0143] (Polyester resin)

[0144] Polyester resin can be obtained by copolymerizing an acid component with a diol component. As the acid component, phthalic acid, terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, cyclohexane dicarboxylic acid, adipic acid and sebacic acid can be exemplified. As the diol component, ethylene glycol, butanediol, pentanediol, hexanediol, neopentyl glycol, diethylene glycol, polytetramethylene glycol, cyclohexanedimethanol and propylene glycol can be exemplified. However, after heat sealing at 260°C-0.5MPa-3s, the crystallinity is preferably 10% or more and less than 70%. This is because when the crystallinity of the polyester is too low, the high-temperature sealing strength cannot be fully exhibited, and when it is too high, the softness tends to become insufficient. According to the above tendency, it is more preferable to use a polyester having a crystallinity of 15% or more and less than 50%. As the polyester resin, it is preferred to use a copolymer obtained by copolymerizing them.

[0145] (Polyamide resin)

[0146] As the polyamide resin, nylon 6, nylon 11, nylon 12, nylon 6,6 and other nylon series can be used. In addition, aromatic amide series having aromatic groups can also be used. As with polyester, the crystallinity after heat sealing is preferably 10% or more and less than 70%, and more preferably 15% or more and less than 50%.

[0147] Furthermore, since polycarbonate and polyphenylene ether are amorphous, there is no preferred range for the crystallinity.

[0148] The polyester, polyamide, and other resins exemplified above may contain at least one or more types. In addition, each resin may be one type or a mixture of multiple types (for example, polyolefin may be a mixture of blocks and random).

[0149] (Modified Polyolefin)

[0150] Examples of the functional group that reacts with the second resin include the following functional groups, but the functional group is not limited to these.

[0151] Polyester: terminal hydroxyl group, terminal carboxyl group, ester bond

[0152] Polyamide: terminal amino group, amide bond

[0153] Polycarbonate: terminal hydroxyl group, ester bond

[0154] Polyphenylene ether: terminal hydroxyl

[0155] Examples of the modifying group that reacts with each of the above functional groups include the following groups.

[0156] Polyester, polycarbonate: hydroxyl, acid-modified (ester) group, aldehyde group, oxazoline group, glycidyl group, amide group, imino group

[0157] Polyamide reaction: hydroxyl, acid-modified (ester) group, aldehyde group, glycidyl group

[0158] Polyphenylene ether reaction: acid-modified (ester) group, oxazoline group, glycidyl group, amide group, imino group

[0159] As specific examples, we can cite:

[0160] Hydroxyl···Poval (Kuraray Co., Ltd.), Melthene-H (Tosoh Corporation) Glycidyl···MODIPER (NOF Corporation), LOTADER, BONDINE (Arkema Inc.)

[0161] Amide group···APOLHYA (Arkema Inc.)

[0162] Imido···ADMER IP (Mitsui Chemicals, Inc.)

[0163] Oxazoline···EPOCROS(Nippon Shokubai Co.,Ltd.)

[0164] etc. are preferred examples.

[0165] In addition, examples of acid-modified polyolefins include acid-modified polyolefins modified with any one of unsaturated carboxylic acids, anhydrides of unsaturated carboxylic acids, and esters of unsaturated carboxylic acids.

[0166] Specific examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid.

[0167] Examples of the anhydride of unsaturated carboxylic acid include anhydrides of unsaturated carboxylic acids such as maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride.

[0168] Examples of the ester of unsaturated carboxylic acid include esters of unsaturated carboxylic acids such as methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethyl maleate, monomethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citraconic acid, dimethyl tetrahydrophthalic anhydride, and dimethyl bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylate.

[0169] As specific products, for example, the following can be used, and maleic anhydride is preferably used.

[0170] Maleic anhydride...ADMER (Mitsui Chemicals, Inc.), MODIC (Mitsubishi Chemical Corporation), TOYO-TAC (Toyobo Co., Ltd.), SANSTACK (Sanyo Chemical Industries, Ltd.)

[0171] Carboxyl···NUCREL, HIMILAN (DuPont-Mitsui Polychemicals Co., Ltd.) ※Ionomers can also be used

[0172] Ester group... EVAFLEX (DuPont-Mitsui Polychemicals Co., Ltd.), LOTADER, BONDINE, EVATANE (Arkema Inc.)

[0173] As the proportion of each resin in the terminal film 40, from the viewpoint of the balance between the high temperature sealing strength and the room temperature sealing strength, the proportion of polyolefin is more preferably 10 to 80wt%. When the total amount of polyolefin and polyester is set to 100wt%, the proportion of polyester is also preferably 90 to 20wt%. In addition, the proportion of modified polyolefin in the polyolefin is preferably 0.1wt% to 100wt%, more preferably 0.5wt% to 40wt%. When the addition amount is too small, the reaction with polyester or polyamide is difficult to proceed. In addition, although there is no problem in performance at 100wt%, when the melting point of the modified polyolefin is low, the high temperature sealing strength may be reduced, so it is more preferably within 40wt%.

[0174] When the terminal film 40 is a multilayer structure, the resin layer 40a can be arranged on the side in contact with the metal terminal 30 or on the side in contact with the packaging material 10. When the terminal film 40 is composed of three or more layers, the resin layer 40a can be arranged between the resin layer 40b and the resin layer 40c (see Figure 5 (c)).

[0175] From the viewpoint of embedding property and insulation property, the thickness of the terminal film 40 is preferably 15 μm or more, more preferably 30 to 300 μm, and further preferably 50 to 200 μm.

[0176] The electrolyte of the all-solid battery can generally use a sulfide electrolyte, an oxide electrolyte, an organic polymer electrolyte, etc. In the case where the electrolyte of the all-solid battery is a sulfide electrolyte, the terminal film 40 preferably contains a hydrogen sulfide adsorbent. When a sulfide electrolyte is used, hydrogen sulfide is generated when water is mixed into the battery, and the sealing force between the metal terminal (tab lead) and the terminal film (tab seal) may be reduced. By adding a hydrogen sulfide adsorbent, the sealing strength at room temperature / high temperature can be maintained even when exposed to hydrogen sulfide.

[0177] Examples of hydrogen sulfide adsorbing substances are not particularly limited, and examples thereof include zinc oxide, amorphous metal silicates, hydroxides of zirconium / lanthanide elements, tetravalent metal phosphates, potassium permanganate, sodium permanganate, aluminum oxide, iron hydroxide, silver sulfate, silver acetate, isocyanate compounds, aluminum silicates, potassium aluminum sulfate, zeolite, activated carbon, amine compounds, ionomers, etc. By making the terminal film 40 contain a hydrogen sulfide adsorbing substance, excellent sealing strength can be maintained at room temperature and high temperature even after exposure to hydrogen sulfide.

[0178] Based on the mass of the terminal film 40, the content of hydrogen sulfide adsorbing substances in the terminal film 40 is preferably 1 to 50 mass %, more preferably 2 to 25 mass %, and further preferably 5 to 15 mass %. By making the content of hydrogen sulfide adsorbing substances in the terminal film 40 not less than 1 mass %, the absorption effect or adsorption effect of hydrogen sulfide can be exerted. On the other hand, by making it not more than 50 mass %, the terminal film 40 can have both tightness and sealant adaptability. In the case where the terminal film 40 has a multi-layer structure, from the viewpoint of tightness to the metal terminal 30, the layer in contact with the metal terminal 30 preferably does not contain hydrogen sulfide adsorbing substances. That is, the layer in contact with the packaging material 10 (for example, Figure 5 (b) The resin layer 40a or Figure 5 The resin layers 40a and 40c in (c) preferably contain a hydrogen sulfide adsorbing substance. When the terminal resin film 40 is composed of three or more layers, the intermediate layer (for example, Figure 5 The resin layer 40a) in (c) preferably contains a hydrogen sulfide adsorbing substance.

[0179] The resin layer 40a contains additives as necessary. Examples of the additives include plasticizers, antioxidants, slip agents, flame retardants, AB agents, light stabilizers, dehydrating agents, and tackifiers.

[0180] As mentioned above, although embodiment of this disclosure was described in detail, this invention is not limited to the said embodiment, Various deformation|transformation and change are possible within the range of the summary of this disclosure described in a claim.

[0181] For example, in the above-mentioned embodiment, a method of providing the anti-corrosion treatment layer 14 only on one surface of the barrier layer 13 (on the second adhesive layer 17 side) is exemplified, but the anti-corrosion treatment layer 14 may also be provided on the other surface of the barrier layer 13 (on the first adhesive layer 12 side). In addition, for example, in the case where the sealant layer 16 is adhered to the barrier layer 13 by thermal lamination, the second adhesive layer 17 may be absent. In the case where the base material layer 11 is provided by coating or applying, the first adhesive layer 12 may not be provided. In the above-mentioned embodiment, an all-solid-state battery is exemplified as a storage device to which the packaging material 10 is applied, but the packaging material 10 may also be appropriately applied to other storage devices (such as lithium-ion batteries).

[0182] Example

[0183] Hereinafter, the present disclosure will be described in more detail based on examples, but the present disclosure is not limited to the following examples.

[0184] <Examples 1A to 14A and Comparative Examples 1A to 5A>

[0185] [Materials used]

[0186] In order to produce the resin films for terminals according to Examples and Comparative Examples, the following materials were prepared.

[0187] [Base resin material]

[0188] Polyester resin 1: a copolymer of terephthalic acid as an acid component and ethylene glycol as a glycol component

[0189] Polyester resin 2: a copolymer of terephthalic acid as an acid component and ethylene glycol and butanediol as diol components

[0190] Polyester resin 3: Copolymer of terephthalic acid and isophthalic acid as acid components and ethylene glycol, butanediol and neopentyl glycol as diol components

[0191] Polyester resin 4: a copolymer of terephthalic acid as an acid component and ethylene glycol and 1,4-cyclohexanedimethanol as diol components

[0192] Polyester resin 5: a copolymer of terephthalic acid and isophthalic acid as acid components and butanediol and hexanediol as diol components

[0193] Polyester resin 6: a copolymer of terephthalic acid and isophthalic acid as acid components and butanediol and hexanediol as diol components (the proportion of butanediol is increased compared to polyester resin 5)

[0194] Polyester resin 7: Copolymer of naphthalene dicarboxylic acid as an acid component and 1,4-cyclohexanedimethanol as a diol component

[0195] Polyester resin 8: Copolymer of terephthalic acid and isophthalic acid as acid components and ethylene glycol and hexanediol as diol components

[0196] Polyolefin resin 1: Amide-modified polyethylene

[0197] Polyolefin resin 2: Random polypropylene

[0198] [Plasticizer]

[0199] · Ethylene glycol diester: 10 parts by mass is mixed with respect to 100 parts by mass of the base resin material as required.

[0200] [Hydrogen sulfide absorbent]

[0201] Zinc oxide: 3 parts by mass is mixed with respect to 100 parts by mass of the base resin material as necessary.

[0202] (Example 1A)

[0203] A terminal resin film (single layer, thickness: 100 μm) composed of the following resin composition was produced by inflation.

[0204] Polyester resin 1: 100 parts by mass

[0205] Plasticizer: 10 parts by mass

[0206] Hydrogen sulfide adsorbent: 3 parts by mass

[0207] (Example 2A)

[0208] A resin film for terminals (single layer, thickness: 100 μm) was prepared in the same manner as in Example 1A except that the polyester resin 2 was used instead of the polyester resin 1.

[0209] (Example 3A)

[0210] A resin film for terminals (single layer, thickness: 100 μm) was produced in the same manner as in Example 1A except that the hydrogen sulfide adsorbing substance was not used.

[0211] (Example 4A)

[0212] A terminal resin film (single layer, thickness: 100 μm) made of the polyester resin 3 was produced by the inflation molding method.

[0213] (Example 5A)

[0214] A terminal resin film (single layer, thickness: 100 μm) was prepared in the same manner as in Example 4A except that a plasticizer (10 parts by mass) and a hydrogen sulfide adsorbent (3 parts by mass) were mixed with the polyester resin 3.

[0215] (Example 6A)

[0216] A resin film for a terminal (single layer, thickness: 100 μm) composed of the polyester resin 4 and the hydrogen sulfide adsorbing substance (3 parts by mass) was produced by the inflation molding method.

[0217] (Example 7A)

[0218] A resin film for a terminal (single layer, thickness: 100 μm) composed of the polyester resin 5 and the hydrogen sulfide adsorbing substance (3 parts by mass) was produced by the inflation molding method.

[0219] (Example 8A)

[0220] A resin film for a terminal (single layer, thickness: 100 μm) composed of the polyester resin 6 and the hydrogen sulfide adsorbing substance (3 parts by mass) was produced by the inflation molding method.

[0221] (Example 9A)

[0222] A resin film for a terminal (single layer, thickness: 100 μm) composed of the polyolefin resin 1 and the hydrogen sulfide adsorbing substance (3 parts by mass) was produced by the inflation molding method.

[0223] (Example 10A)

[0224] A two-layer structured resin film for terminals (50 μm / 50 μm) was produced by the inflation molding method.

[0225] Layer on the packaging material side: polyester resin 1 and hydrogen sulfide adsorbent (3 parts by mass)

[0226] · Layer on the metal terminal side: Polyester resin 7

[0227] (Example 11A)

[0228] A three-layered resin film for terminals (25 μm / 50 μm / 25 μm) was produced by the inflation molding method.

[0229] Layer on the packaging material side: polyester resin 2, plasticizer (10 parts by mass) and hydrogen sulfide adsorbent (3 parts by mass)

[0230] Middle layer: polyester resin 1, plasticizer (10 parts by mass) and hydrogen sulfide adsorbent (3 parts by mass)

[0231] Metal terminal side layer: polyester resin 2 and plasticizer (10 parts by mass)

[0232] (Example 12A)

[0233] A three-layered resin film for terminals (25 μm / 50 μm / 25 μm) was produced by the inflation molding method.

[0234] · Layer on the sealing material side: Polyester resin 1 and plasticizer (10 parts by mass)

[0235] Middle layer: polyester resin 8 and hydrogen sulfide adsorbing material (3 parts by mass)

[0236] Metal terminal side layer: polyester resin 1 and plasticizer (10 parts by mass)

[0237] (Example 13A)

[0238] A two-layer structured resin film for terminals (50 μm / 50 μm) was produced by the inflation molding method.

[0239] Layer on the packaging material side: polyester resin 1, plasticizer (10 parts by mass) and hydrogen sulfide adsorbent (3 parts by mass)

[0240] · Layer on the metal terminal side: Polyester resin 8

[0241] (Example 14A)

[0242] A three-layered resin film for terminals (25 μm / 50 μm / 25 μm) was produced by the inflation molding method.

[0243] · Layer on the sealing material side: Polyester resin 7

[0244] Middle layer: polyester resin 1, plasticizer (10 parts by mass) and hydrogen sulfide adsorbent (3 parts by mass)

[0245] · Layer on the metal terminal side: Polyester resin 7

[0246] (Comparative Example 1A)

[0247] A resin film for a terminal (single layer, thickness: 100 μm) composed of the polyester resin 7 and the hydrogen sulfide adsorbing substance (3 parts by mass) was produced by the inflation molding method.

[0248] (Comparative Example 2A)

[0249] A resin film for a terminal (single layer, thickness: 100 μm) composed of the polyester resin 1 and the hydrogen sulfide adsorbing substance (3 parts by mass) was produced by the inflation molding method.

[0250] (Comparative Example 3A)

[0251] A resin film for a terminal (single layer, thickness: 100 μm) composed of the polyester resin 8 and the hydrogen sulfide adsorbing substance (3 parts by mass) was produced by the inflation molding method.

[0252] (Comparative Example 4A)

[0253] A terminal resin film (single layer, thickness: 100 μm) made of a polyolefin resin 2 was produced by inflation molding.

[0254] (Comparative Example 5A)

[0255] A three-layered resin film for terminals (25 μm / 50 μm / 25 μm) was produced by the inflation molding method.

[0256] · Layer on the sealing material side: Polyester resin 7

[0257] Middle layer: polyester resin 8 and hydrogen sulfide adsorbing material (3 parts by mass)

[0258] · Layer on the metal terminal side: Polyester resin 7

[0259] <Evaluation>

[0260] The following evaluation tests were performed on the resin films for terminals obtained in Examples and Comparative Examples.

[0261] [Loss tangent tanδ of terminal resin film]

[0262] The terminal resin film is cut into 10mm (TD) × 30mm (MD) to obtain a test piece. The test piece is held in a manner where the distance between the clamps is 20mm. According to the method based on JIS K7244-4, a dynamic viscoelasticity device (manufactured by SII, trade name: DMS6100) is used to measure under the following conditions, and the loss tangent tanδ is calculated based on the loss elastic modulus E" and the storage elastic modulus E'. In addition, the temperature of the secondary dispersion peak γ and the temperature of the main dispersion peak α are calculated based on the obtained tanδ curve. The results are shown in Tables 1 to 3.

[0263] Peeling mode: stretching

[0264] Heating rate: 2℃ / min

[0265] Temperature range: -150~150℃

[0266] Frequency: 1.0Hz

[0267] [Initial sealing strength]

[0268] A chemically converted aluminum plate (50 mm × 50 mm) was prepared. On the other hand, a terminal resin film was cut into 50 mm (TD) × 100 mm (MD) to obtain a test piece. The test piece was folded in half and an aluminum plate was placed in the middle. Using a sealing rod with a width of 10 mm, one side of the laminate (test piece / aluminum plate / test piece) was heat-sealed at 165°C, 0.6 MPa, and 10 seconds. Then, the heat-sealed portion was cut into a width of 15 mm to obtain a measurement sample (refer to Figure 6 ). The seal strength was measured at room temperature (23°C) at a peeling speed of 50 mm / min. Based on the results, the evaluation was performed according to the following criteria. The results are shown in Tables 1 to 3. It should be noted that Figure 6 In the figure, the shaded portion is the heat-sealed portion, and the portion with a width of 15 mm is the strength measurement portion.

[0269] A: Bursting strength is 25N / 15mm or more

[0270] B: Bursting strength is 20N / 15mm or more and less than 25N / 15mm

[0271] C: Bursting strength is 15N / 15mm or more and less than 20N / 15mm

[0272] D: Bursting strength is less than 15N / 15mm

[0273] [High temperature seal strength]

[0274] An aluminum plate (50mm×50mm) after chemical conversion treatment was prepared. On the other hand, the resin film for the terminal was cut into 50mm (TD)×100mm (MD) to obtain a test piece. The test piece was folded in half and an aluminum plate was placed in the middle. Using a sealing rod with a width of 10mm, one side of the laminate (test piece / aluminum plate / test piece) was heat-sealed at 165°C, 0.6MPa, and 10 seconds. Then, the heat-sealed part was cut into a width of 15mm and left to stand at 150°C for 5 minutes, and then the sealing strength was measured at a peeling speed of 50mm / min at 150°C. Based on the results, evaluation was performed according to the following criteria. The results are shown in Tables 1 to 3.

[0275] A: Bursting strength is 15N / 15mm or more

[0276] B: Bursting strength is 10N / 15mm or more and less than 15N / 15mm

[0277] C: Bursting strength is 5N / 15mm or more and less than 10N / 15mm

[0278] D: bursting strength is less than 5N / 15mm

[0279] [Seal strength after exposure to hydrogen sulfide (at room temperature)]

[0280] An aluminum plate (50 mm × 50 mm) after chemical conversion treatment was prepared. On the other hand, the resin film for the terminal was cut into 50 mm (TD) × 100 mm (MD) to obtain a test piece. The test piece was folded in half and an aluminum plate was placed in the middle. Using a sealing rod with a width of 10 mm, one side of the laminate (test piece / aluminum plate / test piece) was heat-sealed at 165°C, 0.6 MPa, and 10 seconds. Then, the heat-sealed portion was cut into a width of 15 mm and left to stand for 72 hours at room temperature with a hydrogen sulfide concentration of 20 ppm, and the sealing strength was measured at a peeling speed of 50 mm / min at room temperature. Based on the results, evaluation was performed according to the following criteria. The results are shown in Tables 1 to 3.

[0281] A: Bursting strength is 25N / 15mm or more

[0282] B: Bursting strength is 20N / 15mm or more and less than 25N / 15mm

[0283] C: Bursting strength is 15N / 15mm or more and less than 20N / 15mm

[0284] D: Bursting strength is less than 15N / 15mm

[0285] [Seal strength after exposure to hydrogen sulfide (at 150°C)]

[0286] An aluminum plate (50 mm × 50 mm) after chemical conversion treatment was prepared. On the other hand, the resin film for the terminal was cut into 50 mm (TD) × 100 mm (MD) to obtain a test piece. The test piece was folded in half and an aluminum plate was placed in the middle. Using a sealing rod with a width of 10 mm, one side of the laminate (test piece / aluminum plate / test piece) was heat-sealed at 165°C, 0.6 MPa, and 10 seconds. Then, the heat-sealed portion was cut into a width of 15 mm and allowed to stand for 72 hours at room temperature with a hydrogen sulfide concentration of 20 ppm. Then, after standing for 5 minutes at 150°C, the sealing strength was measured at a peeling speed of 50 mm / min at 150°C. Based on the results, evaluation was performed according to the following criteria. The results are shown in Tables 1 to 3.

[0287] A: Bursting strength is 15N / 15mm or more

[0288] B: Bursting strength is 10N / 15mm or more and less than 15N / 15mm

[0289] C: Bursting strength is 5N / 15mm or more and less than 10N / 15mm

[0290] D: bursting strength is less than 5N / 15mm

[0291] [Table 1]

[0292]

[0293] [Table 2]

[0294]

[0295] [Table 3]

[0296]

[0297] In Tables 1 to 3, the case where there is no D in the evaluation results is considered to be excellent in overall quality. In Examples 1A to 14A, the evaluation of the seal strength is A to C. In contrast, in Comparative Examples 1A to 5A, part of the evaluation of the seal strength is D. Specifically, in Comparative Example 1A, the evaluation of the seal strength at room temperature (initial and after exposure to hydrogen sulfide) is D. It is speculated that this is because the temperature of the secondary dispersion peak γ is higher than the range of -130°C to -50°C, and the temperature of the main dispersion peak α is also higher than the range of 30°C to 130°C. In Comparative Example 2A, the evaluation of the seal strength at room temperature (initial and after exposure to hydrogen sulfide) is also D. It is speculated that this is because the temperature of the secondary dispersion peak γ is higher than the range of -130°C to -50°C. In Comparative Example 3A, the evaluation of the seal strength in a 150°C environment before and after exposure to hydrogen sulfide is D. It is speculated that this is because the temperature of the secondary dispersion peak γ is lower than the range of -130°C to -50°C. In Comparative Example 4A, the seal strength evaluations in a 150°C environment before and after exposure to hydrogen sulfide were all D. This is presumably because the temperature of the secondary dispersion peak γ was lower than the range of -130°C to -50°C, and the temperature of the main dispersion peak α was also lower than the range of 30°C to 130°C. In Comparative Example 5A, the seal strength evaluations were all D.

[0298] <Examples 1B to 28B and Comparative Examples 1B to 4B>

[0299] [Materials used]

[0300] In order to produce the terminal films according to the examples and comparative examples, the following materials were prepared.

[0301] [Resin material]

[0302] · Polyolefin (block polypropylene): manufactured by NOVATEC PP and Japan Polypropylene Corporation

[0303] Polyester 1: Copolymer of terephthalic acid as an acid component and ethylene glycol as a glycol component

[0304] Polyester 2: A copolymer of terephthalic acid as an acid component and ethylene glycol as a glycol component (the amount of ethylene glycol component is increased compared to polyester 1)

[0305] Polyester 3: Copolymer of naphthalene dicarboxylic acid as an acid component and ethylene glycol as a diol component

[0306] · Polyester 4: A copolymer of terephthalic acid as an acid component and ethylene glycol, butanediol and 1,4-cyclohexanedimethanol as diol components

[0307] Polyester 5: A copolymer of naphthalene dicarboxylic acid as an acid component and ethylene glycol as a diol component (the amount of ethylene glycol component is reduced compared to polyester 3)

[0308] · Polyamide (Nylon 6 (Ny6)): GLAMIDE, manufactured by Toyobo

[0309] · Polycarbonate: Iupilon, manufactured by Mitsubishi Chemical Corporation

[0310] Polyphenylene ether: XYRON, manufactured by Asahi Kasei

[0311] Modified polyolefin 1 (maleic anhydride): TOYO-TAC (PP), manufactured by Toyobo

[0312] Modified polyolefin 2 (hydroxy): Melthene, manufactured by TOSOH Corporation

[0313] Modified polyolefin 3 (carboxyl): NUCREL, manufactured by DuPont-Mitsui Polychemicals Co., Ltd.

[0314] Modified polyolefin 4 (ester group): EVATANE, manufactured by Arkema Inc.

[0315] In addition, polyolefin (modified polyolefin) and polyester etc. are melt-mixed in advance by a twin-screw mixer.

[0316] [Hydrogen sulfide absorbent]

[0317] Zinc oxide: 3 parts by weight based on the weight of the terminal film.

[0318] [Evaluation method]

[0319] (Sample preparation)

[0320] The above resin material is used as a sample of each embodiment, cut into 50mm (TD) × 100mm (MD) to make a terminal film sample, cut into 50mm × 50mm and perform chemical conversion treatment AL, then fold two pieces together and heat seal one side with a sealing rod with a width of 10mm at 165℃, 0.6MPa, and 10 seconds. Then, cut the heat-sealed part into a width of 15mm. The general shape of the sample is referred to Figure 6 .

[0321] (Initial heat seal strength)

[0322] The seal strength of the prepared samples was measured at a speed of 50 mm / min under room temperature. The results were ranked as follows.

[0323] A: Bursting strength is 25N / 15mm or more

[0324] B: Bursting strength is 20N / 15mm or more and less than 25N / 15mm

[0325] C: Bursting strength is 15N / 15mm or more and less than 20N / 15mm

[0326] D: Bursting strength is less than 15N / 15mm

[0327] (Initial heat seal strength after exposure to hydrogen sulfide)

[0328] The prepared samples were left to stand at room temperature for 72 hours in an environment with a hydrogen sulfide concentration of 20 ppm, and the sealing strength was measured at a speed of 50 mm / min. The results were ranked as follows.

[0329] A: Bursting strength is 25N / 15mm or more

[0330] B: Bursting strength is 20N / 15mm or more and less than 25N / 15mm

[0331] C: Bursting strength is 15N / 15mm or more and less than 20N / 15mm

[0332] D: Bursting strength is less than 15N / 15mm

[0333] (High temperature heat seal strength)

[0334] The prepared sample was left to stand for 5 minutes in an environment of 150° C., and then the seal strength was measured at a speed of 50 mm / min in an environment of 150° C. The results were ranked as follows.

[0335] A: Bursting strength is 15N / 15mm or more

[0336] B: Bursting strength is 10N / 15mm or more and less than 15N / 15mm

[0337] C: Bursting strength is 5N / 15mm or more and less than 10N / 15mm

[0338] D: bursting strength is less than 5N / 15mm

[0339] (High temperature heat seal strength after exposure to hydrogen sulfide)

[0340] The prepared samples were left standing at room temperature for 72 hours in an environment with a hydrogen sulfide concentration of 20 ppm and at 150° C. for 5 minutes, and then the sealing strength was measured at a speed of 50 mm / min in an environment with 150° C. The results were ranked as follows.

[0341] A: Bursting strength is 15N / 15mm or more

[0342] B: Bursting strength is 10N / 15mm or more and less than 15N / 15mm

[0343] C: Bursting strength is 5N / 15mm or more and less than 10N / 15mm

[0344] D: bursting strength is less than 5N / 15mm

[0345] The resin compositions and evaluation results of Examples 1B to 28B and Comparative Examples 1B to 4B, which were samples with different resin compositions, are summarized in Tables 4 to 6. In each evaluation, no D grade was evaluated as excellent overall quality.

[0346] [Table 4]

[0347]

[0348] [Table 5]

[0349]

[0350] [Table 6]

[0351]

[0352] From the results shown in Tables 4 to 6, it can be confirmed that in each example, excellent quality can be obtained under any of the four conditions of initial heat seal strength, initial heat seal strength after exposure to hydrogen sulfide, high temperature heat seal strength, and high temperature heat seal strength after exposure to hydrogen sulfide. On the other hand, in each comparative example, for example, comparative examples 1B and 2B composed only of polyolefin resins have poor high temperature sealing properties, and comparative example 3B composed only of polyester resin and comparative example 4B composed only of polyamide resin have poor initial seal strength, and thus have insufficient quality.

[0353] Industrial Applicability

[0354] According to one aspect of the present disclosure, a terminal resin film capable of achieving both a sealing strength at high temperature and an initial sealing strength at a sufficiently high level and a method for selecting the same are provided. In addition, according to the present disclosure, a storage device using the above-mentioned terminal resin film is provided. According to other aspects of the present disclosure, a terminal film for storage devices capable of achieving both a sealing strength at high temperature and an initial sealing strength at room temperature at a sufficiently high level is provided.

[0355] Explanation of symbols

[0356] 10 ... packaging material for power storage device, 11 ... base material layer, 12 ... first adhesive layer, 13 ... barrier layer, 14 ... anti-corrosion treatment layer, 16 ... sealing agent layer, 16a ... first resin layer, 16b ... second resin layer, 16c ... third resin layer, 17 ... second adhesive layer, 30 ... metal terminal, 40 ... resin film for terminal, 40a, 40b, 40c ... resin layer, 50 ... power storage device body, 100 ... power storage device

Claims

1. A terminal resin film, the terminal resin film being arranged in a power storage device including a power storage device body and a terminal electrically connected to the power storage device body so as to cover a portion of an outer peripheral surface of the terminal, The terminal resin film has a single-layer structure or a multi-layer structure. A resin layer having at least one secondary dispersion peak γ in the range of -130°C to -74°C of a loss tangent tanδ curve obtained by dynamic viscoelasticity measurement under 1.0 Hz, The resin layer contains a polyester resin or an amide-modified polyolefin resin.

2. The resin film for terminals according to claim 1, wherein The resin layer has at least one main dispersion peak α within a range of 30° C. to 130° C. on the tan δ curve.

3. The resin film for terminals according to claim 1 or 2, wherein The resin layer contains a plasticizer.

4. The resin film for terminals according to any one of claims 1 to 3, Contains hydrogen sulfide adsorbing substances.

5. A method for selecting a terminal resin film, the method comprising: (A) a step of measuring the dynamic viscoelasticity of a terminal resin film to be evaluated at 1.0 Hz; as well as (B) a step of determining whether or not there is at least one secondary dispersion peak γ in the range of -130°C to -74°C of the tan δ curve obtained by the dynamic viscoelasticity measurement.

6. An electric storage device comprising: Power storage device body, A terminal extending from the power storage device body, a packaging material that holds the terminal and accommodates the power storage device body, and The resin film for terminals according to any one of claims 1 to 4, which is disposed between the terminal and the sealing material.

7. The power storage device according to claim 6, wherein: The packaging material has a laminated structure including at least a substrate layer, a barrier layer, and a sealant layer in sequence. The sealant layer has at least one secondary dispersion peak γ in the range of -130°C to -50°C of a loss tangent tan δ curve obtained by dynamic viscoelasticity measurement under a condition of 1.0 Hz.

8. The power storage device according to claim 7, wherein: The sealant layer has at least one main dispersion peak α within a range of 30° C. to 130° C. on the tan δ curve.

9. The power storage device according to claim 7 or 8, wherein: The sealant layer contains a plasticizer.

10. The power storage device according to any one of claims 7 to 9, wherein: The sealant layer contains a hydrogen sulfide adsorbing substance.

11. The power storage device according to any one of claims 7 to 10, further comprising an adhesive layer disposed between the barrier layer and the sealant layer, The adhesive layer contains a hydrogen sulfide adsorbing substance.

12. The power storage device according to any one of claims 7 to 11, The invention further comprises an anti-corrosion treatment layer provided on at least one surface of the barrier layer.

Citation Information

Patent Citations

  • Manufacturing method of lead wire member with sealing film

    JP2008004316A

  • Electrical parts, nonaqueous electrolyte battery, and lead wire and sealing container used for them

    JP2009259739A

  • Gripping method for lead conductor, manufacturing method for lead member, and fixing jig used for manufacture

    JP2010218766A

  • External facing material for power storage device

    JP2013101765A